2017
DOI: 10.1172/jci96036
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 stimulates phosphatidylcholine synthesis to promote triglyceride secretion

Abstract: Conflict of interest: M. Wan is currently an employee of Agios Pharmaceuticals. M.J. Birnbaum is an employee of Pfizer Inc. P.M. Titchenell receives research funding from Pfizer Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 45 publications
(54 reference statements)
13
58
0
Order By: Relevance
“…Long-chain polyunsaturated phosphatidylcholines, diacylglycerols, and phosphatidylethanolamine species were identified as key lipid classes contributing to the observed clustering (Figures 4E–4H). These experiments were consistent with the notion that key enzymes of PC, PE, and VLDL synthesis are targets of both mTOR and Xbp1 regulation (Quinn et al, 2017; Sriburi et al, 2004; Wang et al, 2012) and had been detected as being posttranslationally modified in the phospho-proteomic screen described above.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Long-chain polyunsaturated phosphatidylcholines, diacylglycerols, and phosphatidylethanolamine species were identified as key lipid classes contributing to the observed clustering (Figures 4E–4H). These experiments were consistent with the notion that key enzymes of PC, PE, and VLDL synthesis are targets of both mTOR and Xbp1 regulation (Quinn et al, 2017; Sriburi et al, 2004; Wang et al, 2012) and had been detected as being posttranslationally modified in the phospho-proteomic screen described above.…”
Section: Resultssupporting
confidence: 86%
“…Given that hepatic mTOR signaling and Xbp1 splicing are linked to hepatic lipid metabolism (Lee et al, 2008; Li et al, 2010; Quinn et al, 2017), we also compared the effect of refeeding and food perception on hepatic lipid profiles. Untargeted lipidomic profiling on liver tissue of mice that were fasted, exposed to caged food, or refed for 30, 60, 120, or 240 min revealed that the dominant lipid classes detected were phosphatidylcholines, triacylglycerols, phosphatidylethanolamines, and diacylglycer-ols (Figures 4A–4C; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…We observed a concomitant decrease in CTL1 protein expression that was driven by Slc44a1 mRNA translational repression. Although it has been shown that mechanistic target of rapamycin complex 1 is able to control hepatic PC levels through translational regulation of CCTα, (46) CTL1 was not examined. Moreover, while the observed reduction in both CTL1 protein content and functional choline transport in vivo remains correlative, understanding the specific translational control of choline and lipid metabolism genes and the importance of CTL1 to hepatic phospholipid metabolism during obesity remain relevant future questions.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial activation of hepatic mTORC1 promotes VLDL-TG secretion by stimulating phosphocholine cytidylyltransferase α (CCTα) activity, the rate-limiting step in the synthesis of phosphatidylcholines (PCs), which are used as the amphipathic molecules that stabilize the TG core of VLDL. (28) In this connection, in cultured mouse hepatocytes under nutrient restriction, changes in PC composition of cellular membranes lead to the formation of Them2/PC-TP complex, which directly suppresses mTORC1 signaling by interacting with tuberous sclerosis complex 2 (TSC2) to stabilize the TSC1-TSC2 complex. (6) However, when FAs are abundant, the Them2/PC-TP complex functions to promote the synthesis of PC for ER membranes.…”
Section: Discussionmentioning
confidence: 99%